SYARAT PERLU LAPANGAN PEMISAH - Irawanto, bambang (MATEMATIKA, 2001)
﻿﻿Field is integral domain and is a such that every non-zero elemen in it has multiplicative inverse. Extension field F of field K is splitting field of collections polinomial fi(x) | i Î I of K if F is the smallest subfield containing K and all the zeros in of the polinomial fi(x). Elemen a Î F is algebra over K if f (a) = 0 for some 0 ¹ f (x) Î K[x]. Splitting field is extension algebra.